2016
DOI: 10.12973/eurasia.2016.1207a
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Usability of the Educational Software on Concept Education for Young Children with Impaired Hearing

Abstract: Early intervention and early education have a special place in educating the children with Impaired Hearing (IH). The advancements in information and communication technologies have led to adopting the view that such technologies could be applied in the educational process of the children with IH. Besides, the positive results acquired in the studies conducted in the light of this review have brought up the fact that proper technology-based educational environments should be provided and popularized for the yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…AR-based wearables can be worn on the body because of their lightweight design. They collect information from the user, such as physiological signals, and pass it through cloud computing to obtain realtime data (Berlyne, 1965;Tekedere & Göke, 2016). AR can combine and integrate real and virtual objects in real-life environments and interact with users in real time (Azuma et al, 2001); by integrating teaching content with AR, learners' concentration and knowledge acquisition can be enhanced (Alkhamisi & Monowar, 2013;Barreira et al, 2012;Liu et al, 2020;Yu et al, 2019).…”
Section: Augmented Reality-based Wearables and Digital Educationmentioning
confidence: 99%
“…AR-based wearables can be worn on the body because of their lightweight design. They collect information from the user, such as physiological signals, and pass it through cloud computing to obtain realtime data (Berlyne, 1965;Tekedere & Göke, 2016). AR can combine and integrate real and virtual objects in real-life environments and interact with users in real time (Azuma et al, 2001); by integrating teaching content with AR, learners' concentration and knowledge acquisition can be enhanced (Alkhamisi & Monowar, 2013;Barreira et al, 2012;Liu et al, 2020;Yu et al, 2019).…”
Section: Augmented Reality-based Wearables and Digital Educationmentioning
confidence: 99%
“…The utilization of technological advancement available nowadays has allowed both teachers and students to have better and more effective ways of learning geometry. According to Goker, Ozaydin, and Tekedere (2016), with the proper colours and interfaces, video-assisted topic explanations, questions to reinforce the subjects, and entertainment games with audio-visual feedback, educational software could contribute uniquely to children's learning. The teacher can effectively address the challenge of organizing mathematics instruction to attract and develop the abilities of the most significant possible number of students (Abdul Halim 2013;NCTM, 2000).…”
Section: Importance Of the Problemmentioning
confidence: 99%
“…Rapid technological innovations in the "digital age" need to be considered when discussing the use of technology for educational purposes (Silman et al, 2017). Notably, computer-based practices are becoming increasingly popular since they shorten learning periods for students, increase student motivation, and support students' learning processes (Goker et al, 2016). Hasselbring and Glaser (2000) indicated that new computer-based technology allows rapid access to information, communication, and culture for students with disabilities.…”
Section: Introductionmentioning
confidence: 99%